Meanings come in six - Luure, Andres (Sign Systems Studies, 2008)
Though it seems to be reasonable to restrict the scope of semiotics, in order more completely to understand the semiotic phenomena it is necessary to specify all conceivable types of sign and meaning. The method of sextets is introduced that yields a uniform six-item structure of both general and special sign typologies. A general typology of signs and meanings in language and speech and a typology of referring are presented as the paradigms for the structure. In any sign typology in the framework of this structure, the categorisation of the unit of meaning is analogous to the first three items of the first paradigm. In any sign typology in this framework, the relation between the sign and the meaning is analogous to the relation of referring.